Respuesta :

Answer:

Step-by-step explanation:

Considering the given triangle EDI, to determine ED, we would apply the sine rule. It is expressed as

a/SinA = b/SinB = c/SinC

Where a, b and c are the length of each side of the triangle and angle A, Angle B and angle C are the corresponding angles of the triangle. Likening it to the given triangle, the expression becomes

ED/SinI = DI/SinE = EI/SinD

Therefore

Recall, the sum of the angles in a triangle is 180°. Therefore,

I° = 180 - (36 + 87) = 57°

Therefore,

ED/Sin 57 = 26/Sin 36

Cross multiplying, it becomes

EDSin36 = 26Sin57

0.588ED = 26 × 0.839

0.588ED = 21.814

ED = 21.814/0.588

ED = 37.1 m

ACCESS MORE